Gouritz Cluster Biosphere Reserve : towards sustainability - Urban, Boris; Beswick, Claire (London : Wits Business School, 2018)
The Gouritz Cluster Biosphere Reserve (GCBR), an international biosphere reserve programme, is an initiative of the United Nations Educational, Scientific and Cultural Organization (UNESCO). UNESCO describes these reserves as learning sites for sustainable development, saying: Biosphere reserves harmonize conservation of biological and cultural diversity, and economic and social development, through partnerships between people and nature. They also contribute to the transition to green societies by experimenting with green development options such as sustainable tourism and training for eco-jobs.This case situates Wendy Crane, who has for many years been involved in the conservation efforts of the GCBR, savouring the view of the Langeberg Mountains from her office on her farm in the Eden District of South Africa's Western Cape province. Her pleasure is diminished by the knowledge that, like so many parts of the GCBR, the environment of this area is under threat. She is preparing for a meeting in March 2017 of the board of the non-profit company (NPC) that seeks to initiate and coordinate activities to achieve the goals of the GCBR.The NPC board members want the organisation to be self-sustaining when it comes to core costs. To this end, the board has established Gouritz Enterprises. This social enterprise will be responsible for profit-driven activities that will fund the NPC's core costs. The enterprise has not yet started work in any formal way, and Crane is not sure if establishing a separate profit-driven entity is the best way of achieving the self-financing goal.
Originally Published InUrban, B., & Beswick, C. (2018). Gouritz Cluster Biosphere Reserve: Towards sustainability. WBS-2017-8. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Gouritz Cluster Biosphere Researve; Unesco; Biosphere; Sustainable development